Collaborative Governance Model In Land Building Asset Management - Rovinus Tallulembang; Tri Oldy Rotinsulu; George M.V. Kawung; Agnes L.Ch.P. Lapian (Citakonsultindo, 2026)
Land and building asset management is a strategic aspect of local government governance aimed at accountability and optimal asset utilization. However, challenges such as weak coordination, limited resources, and low stakeholder participation persist. This study aims to analyze and formulate a collaborative governance model in managing land and building assets. This research uses a qualitative descriptive approach with literature study and document analysis techniques. The results indicate that collaborative governance enhances asset management effectiveness through synergy among government, private sector, and community. The proposed model consists of dialogue, joint planning, collaborative implementation, and continuous evaluation. Strengthening institutions, transparency, and digital-based information systems are recommended to support collaboration.